Experiment Social Media Marketing Strategy Kreator Pass - wiyandi wiyandi; Muhammad Ardyansyah (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The newly developing Startup C business has difficulty being recognized by many people in the field of internet industry technology. As the times become more modern, businesses must be able to adapt to the latest technological information with businesses that are attractive today. Many newly developing businesses use social media platforms as a place to seek fame to increase the Brand Awareness of their businesses, such as using Intagram, Tiktok, Youtube. This research was conducted using qualitative methods through interviews (open-ended). The research produced analytical data that Tiktok gained viewers and gave positive comments on the development of the Kreator Pass business. Analytics data for Youtube gained quite high fame and supported the Kreator Pass business while analytics on Instagram got negative results, lacking a supportive audience. From the data obtained, promoted videos need to be more interesting to watch in order to trigger the attention of viewers